2016
DOI: 10.21010/ajtcam.v13i6.3
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNO-MODULATORY PROPERTIES OF PREBIOTICS EXTRACTED FROM Vernonia amygdalina

Abstract: Background: Vernonia amygdalina, commonly called bitter-leaf, is widely consumed in many parts of Africa, and Nigeria, in particular. The leaf extract has been reported to have antimicrobial, anti-plasmodial, anti-helminthic, as well as prebiotic properties, but its immuno-modulatory effects have not been well-studied, neither have the prebiotics been identified. This study evaluated the immuno-modulatory properties of the aqueous leaf extract and identified the prebiotic components. Methods: The immuno-modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The potential of N. sativa to modulate B cell-mediated immune response while balancing Th1/Th2 ratio to potentiate T cells-mediated immune response merits further investigation. This activity can be explored as an adjunct to potential vaccine candidates to mediate meaningful and sustained immune response post vaccination (Petrovsky, 2006), which is one of the main challenges with current (Koley and Lal, 1994;Talwar et al, 1995;Talwar et al, 1997;Badary et al, 1998;Hore et al, 1999;Salem and Hossain, 2000;Petrovsky, 2006;Bamosa et al, 2010;Datau et al, 2010;Iyyadurai et al, 2010;Momoh et al, 2010;Salem et al, 2011;Schumacher et al, 2011;Venugopalan et al, 2011;Aljindil, 2012;Choudhary et al, 2012;Momoh et al, 2012;Abdel-Moneim et al, 2013;Li et al, 2013;Mishra and Dave, 2013;Saalu et al, 2013;Adedapo et al, 2014;Nabukenya et al, 2014;Tran et al, 2014;Ulasli et al, 2014;Yee et al, 2014;Gholamnezhad et al, 2015;Majdalawieh and Fayyad, 2015;Ashfaq et al, 2016;George et al, 2016;Im et al, 2016;Omoregie and Pal, 2016;Rehman et al, 2016;Zakaria et al, 2016;Onasanwo et al, 2017;Salem et al, 2017;Tavakkoli et al, 2017;Asante et al, 2019;…”
Section: Medicinal Plants In Covid 19: Efficacy Safety and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of N. sativa to modulate B cell-mediated immune response while balancing Th1/Th2 ratio to potentiate T cells-mediated immune response merits further investigation. This activity can be explored as an adjunct to potential vaccine candidates to mediate meaningful and sustained immune response post vaccination (Petrovsky, 2006), which is one of the main challenges with current (Koley and Lal, 1994;Talwar et al, 1995;Talwar et al, 1997;Badary et al, 1998;Hore et al, 1999;Salem and Hossain, 2000;Petrovsky, 2006;Bamosa et al, 2010;Datau et al, 2010;Iyyadurai et al, 2010;Momoh et al, 2010;Salem et al, 2011;Schumacher et al, 2011;Venugopalan et al, 2011;Aljindil, 2012;Choudhary et al, 2012;Momoh et al, 2012;Abdel-Moneim et al, 2013;Li et al, 2013;Mishra and Dave, 2013;Saalu et al, 2013;Adedapo et al, 2014;Nabukenya et al, 2014;Tran et al, 2014;Ulasli et al, 2014;Yee et al, 2014;Gholamnezhad et al, 2015;Majdalawieh and Fayyad, 2015;Ashfaq et al, 2016;George et al, 2016;Im et al, 2016;Omoregie and Pal, 2016;Rehman et al, 2016;Zakaria et al, 2016;Onasanwo et al, 2017;Salem et al, 2017;Tavakkoli et al, 2017;Asante et al, 2019;…”
Section: Medicinal Plants In Covid 19: Efficacy Safety and Researchmentioning
confidence: 99%
“…This plant was reported to be traditionally used to relieve fever, diarrhoea, cough, and headache ( Plant Resources of Tropical Africa, PROTA, 2004 ). Aqueous extracts of G. amygdalinum showed positive effects in enhancing immune response by increasing the levels of white blood cells and CD4 + ( Momoh et al, 2010 ; Momoh et al, 2012 ; Im et al, 2016 ). With the capability to increase the CD4 + cell counts, this extract was reported to be adjuvant to antiretroviral therapy in HIV positive patients ( Momoh et al, 2012 ).…”
Section: Medicinal Plants In Covid 19: Efficacy Safety and Researchmentioning
confidence: 99%
“…They increase the body's resistance to disease, retard or ease the process of Natural ageing. These compounds are responsible for a green therapeutic effect and they frequently serve as model for the synthesis of new medicine [37].…”
Section: Introductionmentioning
confidence: 99%
“…Continued research on the pharmacological activity of Vernonia amygdalin has demonstrated its immunomodulatory activity in improving the level CD4 counts in both man and animals. Ezeonu et al 20 analyzed the leaf extract of Vernonia amygdalin for its immunological effect in rats and reported a remarkable effect on CD4 count, haematological parameters and lipid profile. Also, Olubumi et al 21 evaluated concoctions containing ten medicinal plants including bitter leaf with potential antidiabetic activity for the presence of toxic elements.…”
mentioning
confidence: 99%